REFORMATION IN 1517 AND TODAY: CONSIDERATIONS FROM TRENT AND VATICAN II - TANNER, NORMAN (Asian Horizons, 2017)
Marking the fifth centenary of the beginning of the Reformation in 1517, this article considers the impact of the two most important councils of the Catholic Church which followed — Trent (1545-63) and Vatican II (1962-5) — upon Catholic-Protestant relations as well as upon world history. Trent’s wide-ranging decrees tackled most major issues raised by the Protestant reformation, yet the council listened to Protestant concerns more than that is usually recognized. The decrees of Vatican II were also wide-ranging, though with a different tone to Trent. They led to a new epoch in relations between the Catholic Church and the Churches of the Reformation as well as between Christianity and the wider world.